Pengembangan Sistem Deteksi Anemia Non-Invasif Menggunakan Photoplethysmography (PPG) dan Logika Fuzzy untuk Estimasi Kadar Hemoglobin - Darojat Yugiantoro; Eka Nuryanto Budisusila; Agus Suprajitno; Arief Marwanto; Abdul Haris Kuspranoto (MEDIKA TRADA, 2025)
The Anemia is a global health issue affecting many individuals worldwide. Traditional anemia detection through invasive blood testing is often costly, time-consuming, and requires trained medical personnel. This study developed a non-invasive anemia detection system based on Photoplethysmography (PPG) technology and fuzzy logic to estimate hemoglobin (Hb) levels and classify the degree of anemia. The system uses a PPG sensor to measure red and infrared light intensities, which are used to calculate the ratio and estimate the hemoglobin levels. The fuzzy logic system then classifies the estimated Hb results into the categories of Severe Anemia, Moderate Anemia, and Mild Anemia. The results of the study indicate that this system provides an estimated hemoglobin level with an accuracy of 88.42%, and can classify anemia degrees with results comparable to conventional blood testing. This system offers a more practical, efficient, and non-invasive alternative for anemia detection and has the potential to be used for self-health monitoring.